2021
DOI: 10.5194/tc-15-3813-2021
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic control on snow avalanche activity in central Spitsbergen

Abstract: Abstract. Atmospheric circulation exerts an important control on a region's snow avalanche activity by broadly determining the mountain weather patterns that influence snowpack development and avalanche release. In central Spitsbergen, the largest island in the High Arctic Svalbard archipelago, avalanches are a common natural hazard throughout the winter months. Previous work has identified a unique snow climate reflecting the region's climatically dynamic environmental setting but has not specifically address… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Previous work in North America (Schauer et al, 2021), Northern Europe (Hancock et al, 2021;Fitzharris and Bakkehøi, 1986) and the Alps (Jomelli et al, 2007) has shown the potential of investigating precursor meteorological data for avalanche prediction using avalanche databases. In HMA such forecasting only exists in the Indian Western Himalaya as of yet.…”
Section: Avalanche Incidents and Impactsmentioning
confidence: 99%
“…Previous work in North America (Schauer et al, 2021), Northern Europe (Hancock et al, 2021;Fitzharris and Bakkehøi, 1986) and the Alps (Jomelli et al, 2007) has shown the potential of investigating precursor meteorological data for avalanche prediction using avalanche databases. In HMA such forecasting only exists in the Indian Western Himalaya as of yet.…”
Section: Avalanche Incidents and Impactsmentioning
confidence: 99%
“…Previous work in North America (Schauer et al, 2021), northern Europe (Hancock et al, 2021;Fitzharris and Bakkehøi, 1986) and the Alps (Jomelli et al, 2007) has shown the potential of investigating precursor meteorological data for avalanche prediction using avalanche databases. In HMA, such forecasting only exists in the Indian western Himalaya as of yet.…”
Section: Avalanche Incidents and Impactsmentioning
confidence: 99%
“…Snow hazards are mainly avalanches and seasonal floods (freshets) derived from rapid snowmelt (Table 2). Avalanches have been examined in many studies in terms of their locations, frequency, and relationships to synoptic climate (Bellaire et al, 2016; Hancock et al, 2021). Avalanche risk under climate change has also been evaluated (Ballesteros‐Cánovas et al, 2018; Beniston et al, 2003; Castebrunet et al, 2014; Höller, 2009; Lazar & Williams, 2008).…”
Section: Hazard Responses To the Changing Mountain Cryospherementioning
confidence: 99%
“…It is therefore the interplay between temperature and precipitation conditions, and their seasonal variations, that determines avalanche response, and this introduces uncertainty into snowpack and avalanche prediction models under climate change (Schmucki et al, 2015). Higher wind speeds can also increase avalanche frequency (Hancock et al, 2021) via snowblow processes, and this may be difficult to predict from RCMs run over complex mountainous terrain. Spatial and temporal variations in snow patterns and thickness also have implications for the volume and timing of snowmelt (and glacier melt) contributions to mountain rivers, and this contribution can vary widely, even between adjacent catchments (e.g., Juen et al, 2007; Kure et al, 2013; Qazi et al, 2020).…”
Section: Hazard Responses To the Changing Mountain Cryospherementioning
confidence: 99%